PERAN KEGIATAN KEAGAMAAN DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK DI SMA NEGERI 2 MALANG - Fahmil Ilmiyah; Abdul Jalil; Sufiyana Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Religious activities in an education play a strong role in shaping the religious character of students, it can be interpreted that character occurs not because it is innate from birth, does not come alone, but must be formed and instilled consciously in students. In the process of character building, students will not take place by themselves, but through a process. One of the processes that can shape the character of students is one of them through religious activities in the school. This study aims to describe the role of religious activities in shaping the religious character of students at SMA Negeri 2 Malang, with three research focuses including: (1) Design of religious activities in shaping the religious character of students at SMA Negeri 2 Malang. (2) Implementation of religious activities in shaping the religious character of students at SMA Negeri 2 Malang. (3) Supporting factors and obstacles to religious activities at SMA Negeri 2 Malang. This research is a qualitative research by taking the background of SMA Negeri 2 Malang. The data collection methods used are observation, interviews and documentation. The sources of this research data are the deputy principal of SMA Negeri 2 Malang, Secretary of religious affairs SMA Negeri 2 Malang, teachers implementing religious activities of SMA Negeri 2 Malang, teachers of PAI SMA Negeri 2 Malang and students of SMA Negeri 2 Malang